U.P. students' perceptions of academic library staff - Depita, Lourdes D. (1980)
This is a study of the perceptions of undergraduate and graduate students enrolled in the twenty colleges of the University of the Philippines in Diliman of the most liked and most disliked characteristics of academic library staff in three dimensions, namely, job competence, interpersonal relationship and physical attributes. The data for the study were supplied by 1,562 students representing 10 percent of the total student population during the second semester, 1977-1978. These students responded to a two-page questionnaire consisting of thirty-one items on seven-point bi-polar scales with each extreme defined by an adjective. This questionnaire was based on the SD (Semantic Differential) technique originally developed by Charles Osgood. This technique was utilized to analyze data, using test of means to rank the traits and D statistics to measure linear distance between the two concepts on each of the scales and by dimension.